Introduction: institutional experimentation for better (or worse) work. (May 2020) - Ferreras, Isabelle; MacDonald, Ian; Murray, Gregor; Pulignano, Valeria
In different national, institutional and organisational contexts, and in conditions of uncertainty, worker organisations, old and new, are experimenting in response to the major fault lines of change they face. This introduction to the special issue focuses on these processes of experimentation: the disruption of traditional forms of regulation of work and employment; how a variety of actors are engaged in experimentation about the governance of work and employment; how these actors are making claims on the state; how these processes can lead to better and to worse work; and how strong sets of capabilities and particular configurations of resources on the part of those engaged in experimentation can contribute to new forms of work regulation and indeed better work. Key themes include the agency and resilience of actors and their development of new collective capabilities, the importance of deliberation and democracy, the strategic and reflexive nature of their experimentation, the potential scalability of experimentation into new forms of institutionalisation integrating core values such as equality, solidarity and democracy, and new models of research aggregation requiring ongoing dialogue between actors and researchers.